the Influence Of Financial Performance On Credit Distribution In Indonesia Stock Exchange-Listed Commercial Banks: Financial Performance On Credit Distribution In Indonesia Stock Exchange-Listed Commercial Banks - Nining Widiyanti; Maulida Laela Luthfiana; Fathonah Eka Susanti (Asian Journal of Management, Entrepreneurship and Social Science, 2022)
Abstract The relatively stagnant credit growth in the last few years has triggered banks in Indonesia to continue to improve quality and prudence so that loans can be channeled properly because it greatly affects the quality of credit and the growth of the bank's own business. Proper credit distribution can increase the profitability of the banking business because the amount of income from the credit sector will affect the amount of profit. This study aims to identify the influence of Third Party Funds, Loan to Deposit Ratio, Capital Adequacy Ratio and Non Performing Loans on lending to commercial banks in Indonesia. Technical data analysis used in this study uses the regression method panel data with a significance level of 5% consisting of 11 commercial bank companies listed on the Indonesia Stock Exchange. The results of data analysis showed that the variable Third Party Funds had a positive and significant effect on commercial bank lending, Loan to Deposit Ratio had a positive and significant effect on commercial bank lending, Capital Adequacy Ratio had a positive and significant effect on commercial bank lending, Non-Performing Loans had a negative and significant effect on commercial bank lending. Keywords: Third Party Funds, Loan to Deposit Ratio, Capital Adequacy Ratio, Non Performing Loans, Credit Distribution